Characterization and diagnosis of the process of reuse of electronic waste: case study in a specialized center in Recife, Pernambuco, Brazil - Ferraz, Paulo Henrique Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The expansion of the electro-electronic products market in Brazil, which occurred in the last decades, resulted in a higher volume of waste from electro electronic equipment (WEEE) generated due to the reduction of the useful life of the devices, having been the seventh largest generator of electronic waste in the country. in 2016. In Recife, an annual generation of 9,841 tons is estimated. Besides having materials of slow degradation, there are also heavy metals in the composition of electronic waste, harmful to the environment and living beings when in high concentration. Some studies have observed the insufficiency of actions by society regarding the correct disposal of WEEE. This research consists of a descriptive case study of the operation dynamics and reception rates of a specialized WEEE recycling center located in Recife, with collection points distributed throughout the city. Data from the first half of 2019 were analyzed. The study found the potential for reuse of donated equipment, as well as a greater contribution from the private sector, possibly reflecting the implementation of the National Solid Waste Policy.